MENINGKATKAN KEMAMPUAN MEMECAHKAN MASALAH BAGI MAHASISWA PGMIPABI DALAM PERKULIAHAN TELKURMAT-2 MELALUI PENERAPANMIND-MAPPING BERCIRI KONSERVASI - Suyitno, Amin; Sugiharti, Endang (Universitas Negeri Semarang, 2013)
Ability to solve problems for students of PGMIPABI Programin Analysis of Mathematics Curriculum 2 stillneeds to be improved.One way of it istoimplementof Mind Mapping based-on Conservationthattrain studentsfor independent study, creatitive, and get to knowthe environment by themselves.The problem ishow to improveproblem-solving abilityfor studentsof PGMIPABIof MathematicsEducation Study Program of UNNES, especiallyin the Analysis of Mathematics Curriculum 2 lecturing. The purposeof this researchis to improve problem-solving abilityfor studentsof PGMIPABIof MathematicsEducation Study Program of UNNES, especiallyin the Analysis of Mathematics Curriculum 2 lecturing.The resultsand conclusionsare asfollows.By applyingof Mind Mapping based-onConservation thenproblem-solving skillsfor studentsof PGMIPABIof MathematicsEducation Study Program of UNNES, especiallyin the Analysis of Mathematics Curriculum 2 lecturing canbe increased. The averagescoreobtained bystudentswas85.6,the averagescorewas higherthanthe averagescore ofthe previous years.The suggestions are (1)development ofapplyingof Mind Mapping based-on Conservation to improve problem-solving abilityfor studentsof PGMIPABIof MathematicsEducation Study Program of UNNES, especiallyin the Analysis of Mathematics Curriculum 2 shouldbe followed. (2)Needafurther research tothe othersubject and learning model base-on conservation.